Information Technology Preparedness in Indonesia’s Future Capital Area - Suryanto, Adi; Nurdin, Nurliah; Sutrisno, Edy; Reza, Izzul Fatchu (KnE Social Sciences, 2022)
The Indonesian capital, DKI Jakarta, will be replaced by Penajam Paser Utara in East Kalimantan, according to the Central Government. Penajam Paser Utara is divided into four districts and thirty villages. The majority of these villages use information technology (information technology), such as websites, to report on village fund applications. However, none of the villages have used information technology to promote the development of the villages’ natural resources potential. Faced with the prospect of becoming Indonesia’s capital, a concerted effort must be made to engage with information technology in order to support the country’s economic development. According to the findings of this study, information technology has only been used to create village fund reports. However, most village functions such as providing certificates for births, marriages, deaths and homes are still reported manually. Penajam Paser Utara public officials have not yet maximized the use of the information technology system to serve the community. Furthermore, no natural resources have been promoted in the village office so that the villagers can earn more money than they did before the introduction of information technology. Keywords: information technology, village development, economic gain and localities